THE ROLE OF MODERN TECHNOLOGY IN THE PROMOTION OF URDU LANGUAGE AND LITERATURE - Dr. Taqwim ul Haq; Dr. Shahabuddin; Dr. Muhammad Sulaiman (Journal of Religion and Society, 2025)
Modern technology has significantly contributed to the promotion and development of Urdu language and literature. The rise of the internet, social media platforms, and digital publishing has created new opportunities for the global reach of Urdu literature. Blogging, vlogging, and online content creation have enhanced the accessibility and popularity of Urdu language among the younger generation. However, technological advancements have also presented certain challenges, including issues related to machine translation, the dominance of Roman Urdu, and the quality of online Urdu content. This paper explores the impact of modern technology on Urdu language and literature, highlighting the opportunities and challenges faced by the Urdu-speaking community. It also provides suggestions for the preservation and promotion of Urdu language through government support, digital archives, and collaboration with global platforms such as Google and Amazon. The findings suggest that modern technology, when used effectively, can play a pivotal role in enhancing the status of Urdu language and literature on a global scale. Keywords:Urdu Language, Urdu Literature, Modern Technology, Digital Publishing, Social Media, Machine Translation, Roman Urdu, Artificial Intelligence